2012
DOI: 10.1111/j.1365-4632.2011.05004.x
|View full text |Cite
|
Sign up to set email alerts
|

What happens to the severity grading by objective SCORAD if we over‐ or underestimate disease extent or intensity in patients with atopic dermatitis?

Abstract: The effect on AD grading is generally small if extent is misestimated. A huge difference, especially if underestimated in the mild group, would occur if intensity is misestimated. Surrogate markers of disease severity could overcome or supplement shortcoming of clinical scores in AD research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
1
3
0
1
Order By: Relevance
“…This shows that the estimation of intensity signs contributed to inter-rater variability of the oSCORAD more than the estimation of disease extent. This may be confirmed by the results of a study performed by Hon et al [21] , which revealed that misestimation of AD intensity, rather than the disease extent, would tremendously alter the severity grading of oSCORAD. Thus, careful assessment of disease intensity is of paramount concern in order to minimize the effect of misestimation.…”
Section: Discussionsupporting
confidence: 76%
“…This shows that the estimation of intensity signs contributed to inter-rater variability of the oSCORAD more than the estimation of disease extent. This may be confirmed by the results of a study performed by Hon et al [21] , which revealed that misestimation of AD intensity, rather than the disease extent, would tremendously alter the severity grading of oSCORAD. Thus, careful assessment of disease intensity is of paramount concern in order to minimize the effect of misestimation.…”
Section: Discussionsupporting
confidence: 76%
“…Patients with severe AD start with higher disease severity and often show less fluctuations, allowing for greater differences in treatment responses. [23][24][25][26][27] The sensitivity of clinical outcome measures generally increases with higher baseline disease activity and shows less reproducibility with lower scores, [23][24][25][26][27] a fact that is now increasingly recognized in trial design.…”
Section: Discussionmentioning
confidence: 99%
“…Although SCORAD is a good instrument for AD, it was also used to be the measurement of efficacy and patient’s condition in the trials of Complementary or Alternative Medicine (CAM) domain, such as Traditional Korean Medicine, TCM and homoeopathic treatment for AD[19-21], however, a huge difference, especially if underestimated in the mild group, would occur if intensity is misestimated when using the SCORAD; Surrogate markers of disease severity could overcome or supplement shortcoming of clinical scores in AD research [22]. As there are no other validated instruments for AD patients in TCM area, we believe that this instrument may be useful in daily clinical practice and scientific research, especially in the area of Complementary or Alternative Medicine (CAM).…”
Section: Discussionmentioning
confidence: 99%